Content Analysis of "Bloom and Shine" Grade 1: Evaluated by Tomlinson's Criteria - Agni Oktavia R., Amanda; Rica Amelia Putri; Asri, Diar Mukti (Journal Of Foreign Language Learning and Teaching, 2025)
This study looks at the Bloom and Shine English textbook for Grade 1 students, using Brian Tomlinson’s sixteen principles of effective language learning materials as a guide. The research uses a qualitative content analysis to see how well the textbook supports these principles. The results show that the textbook does a good job in keeping students engaged, interested, and catering to different learning styles with its colorful pictures, fun topics, and playful activities. However, most of the activities still focus on simple skills like remembering and understanding, with very few chances for students to use real-life English or think critically. This shows the need for more activities that help students develop higher-level thinking skills and use English creatively. This study helps teachers and textbook developers by pointing out areas that could be improved to make learning more meaningful for young learners.